The Time Politics of Refugee Resettlement and Higher Education in the United States - Wolfgram, Matthew; Van Auken, Paul (Refuge: Canada's Journal on Refugees, 2023)
This paper sheds light on experiences within systems of US resettlement and its structures of (un)welcome. There is considerable evidence that the policy framework of these systems complicates the possibilities of higher education for refugees. Drawing on interviews with residents with a refugee background and resettlement service providers, we explore how US refugee resettlement policy creates obstacles for refugees in pursuing higher education and professional work by imposing a particular regimentation of time on refugees’ lives that impels them to rapidly integrate into low-income employment markets. We argue that such a time politics of speed hastens the resettlement process to advance the goal that residents with refugee background obtain rapid economic self-sufficiency and discuss the policy implications.